Biological activity of the aqueous extract of Lychnophora pinaster Mart. - Silveira, D.; Wagner, H.; Chiari, E.; Lombardi, J.a. [UNESP]; Assunção, A.c.; Oliveira, A.b. De; Raslan, D.s. (Sociedade Brasileira de Farmacognosia, 2005)
Lyophilized aqueous extract (LAE) from Lychnophora pinaster Mart (Asteraceae) aerial parts was evaluated in the search of possible biological activities. LAE exhibited trypanocidal activity (113.62 mg/mL), but could not inhibit 5-lipoxygenase in vitro (17% of inhibition). LAE chemical characterization by HPLC with UV-Diode Array Detector showed the presence of caffeic acid, isochlorogenic acid, vitexin, isovitexin and quercetin, in comparison with authentic samples.
Keywords: Lychnophora pinaster; trypanocidal activity; 5-lipoxygenase assay